ANALISIS KEBERLANJUTAN USAHATANI PERKEBUNAN KELAPA RAKYAT DI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Rahmah; Muwardi, Didi; Yusri, Jumatri (JURNAL AGRIBISNIS, 2024)
ABSTRACT Keritang District is one of the coconut production centers in Indragiri Hilir Regency, Riau Province. However, community coconut plantation farming in Indragiri Hilir Regency in recent years has experienced several problems, namely a decrease in land area and coconut production, fluctuating coconut selling prices, and the absence of extension institutions and farmer groups, which can affect the sustainability of community coconut plantation farming. Research objectives (1) analyze and determine the sustainability status of coconut plantation farming; (2) find out the sensitive attributes of people's coconut plantation farming. The research method used was a survey method with a sample size of 98 respondents taken using the purposive sampling method. Data analysis was carried out using the MDS method with RAP-Coconut software. The results of the research show that people's coconut plantation farming in Keritang District, Indragiri Hilir Regency, has a less sustainable status in ecological, economic, and social dimensions. Sensitive attributes in the ecological dimension are pest and disease control, the use of pesticides, and fertilization. Sensitive attributes in the economic dimension are capital institutions, employment, land ownership, and the stability of selling prices. Sensitive attributes in the social dimension are farmers' relationships with marketing actors, farmer groups, age of farmers, availability of extension services, family participation, farmers' views on coconut farming, and level of education. Keywords : Sustainability, farm business, coconut, sensitive attributes